Consumer decision making styles when purchasing laundry washing powder - Mhlongo, Khanyisa Yvonne (University of the Witwatersrand, Johannesburg, 2015)
Detergent products are universal products used in many of South African households across all demographics, irrespective of social standing. They are also relatively higher priced compared to other fast moving consumer goods (FMCG). For this reason the detergents market is significant in terms of value and a percentage of household spending (Thaker & Copestake, 2012). In South Africa, for many years the laundry washing powder market has been dominated by multinationals, manufacturing and distributing many national brands to households for many generations, some for more than 100 years. In recent years, many local manufacturers, including retailers have begun to venture into this market. It is not clear what decision styles influence consumer perceptions, attitudes, intentions towards laundry washing powder, thereby making it difficult for new entrants to become formidable market players. It is therefore important for manufacturers and marketers to understand consumer perceptions, attitudes and behaviours towards shopping, as this leads to correct segmentation, targeting and positioning in a fight for the consumer’s share of the wallet. This study used the Consumer Styles Inventory (CSI) methodology as developed in the USA by (Sproles & Kendall, 1986) to understand the South African consumer personality when purchasing laundry washing powder, using qualitative and quantitative methods to collect data from consumers in the Johannesburg area. The research instrument was adapted from the original instrument developed by (Sproles & Kendall, 1986). This research found that South African consumers are influenced by 4 of the 8 factors identified by (Sproles & Kendall, 1986). The key message manufacturers, markets and retailers is that washing powder consumers are habitual-brand loyal consumers who prefer quality brands; however they are willing to try new brands as long as they are perceived as meeting quality standards. Although they look for value for money, they are not willing to sacrifice quality for price savings. They also engage in impulsive buying, using promotions and discounts to purchase their favourite quality brands.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration, to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2014
Keywords: Consumer behavior; Consumers' preferences; Soap trade; South Africa; UCTD